INTAKE OF A VITAMIN-MINERAL COMPLEX IS A RATIONAL WAY TO MAKE UP A CALCIUM DEFICIENCY IN CONDITIONS OF INSUFFICIENT CONSUMPTION OF DAIRY PRODUCTS BY A CHILD - Evgenia V. Shikh; Anna A. Makhova; Evgeny E. Emelyashenkov (Вопросы современной педиатрии)
A calcium deficiency is detected in more than 80% of children. This is the result of inadequate consumption of milk and dairy products which are the main food sources of calcium. There is a correlation between deficiency of calcium intake with food in childhood and the risk of osteopenia and osteoporosis in subsequent life periods. With insufficient exogenous intake of calcium, its concentration in the blood decreases which stimulates bone resorption. The factors that further limit the consumption of dairy products are lactase deficiency and cow's milk protein allergy. In order to ensure the intake of the necessary amount of calcium, it is advisable to use vitaminmineral complexes in children that contain not only a sufficient amount of calcium and vitamin D but also other micronutrients required for bone formation.